Evaluation of the overdiagnosis in breast screening programmes using a Monte Carlo simulation tool: a study of the influence of the parameters defining the programme configuration. Issue 2 (9th February 2019) - Forastero, Cristina; Zamora, Luis I; Guirado, Damián; Lallena, Antonio M
Abstract : Objectives: To build up and test a Monte Carlo simulation procedure for the investigation of overdiagnosis in breast screening programmes (BSPs). Design: A Monte Carlo tool previously developed has been adapted for obtaining the quantities of interest in order to determine the overdiagnosis: the annual and cumulative number of cancers detected by screening, plus interval cancers, for a population following the BSP, and detected clinically for the same population in the absence of screening. Overdiagnosis is obtained by comparing these results in a direct way. Results: Overdiagnosis between 7% and 20%, depending on the specific configuration of the programme, have been found. These range of values is in agreement with some of the results available for actual BSPs. In the cases analysed, a reduction of 11% at most has been found in the number of invasive tumours detected by screening in comparison to those clinically detected in the control population. It has been possible to establish that overdiagnosis is almost entirely linked to ductal carcinoma in situ tumours. Conclusions: The use of Monte Carlo tools may facilitate the analysis of overdiagnosis in actual BSPs, permitting to address the role played by various quantities of relevance for them.